(3JgPjH eSJeQ GdChgGe Ydi Phi GdeYQaI hChdi GdCagGes - (3Ydj Hf gHI Gddg Hf Ydj Hf LYaQ, CHh fUQ, SYO Gdedc, GHf eGchdG,J (B475 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi JaQO HGdceGd adG fbU ai JeGeg s
(3BNQgG (B:s
(3Je LejY GdcJGH hGdMeO ddg QH GdYGdejf hUdGJg Ydi SjOfG eMeO NGJe GdfHjjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B257s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B101 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI ajV Gddg (B(1583) s
Keywords: (3GdJGQjNs